HYPERTENSION IN CHILDREN WITH OBESITY: A COMPARISON OF THE EFFECTIVENESS OF PHARMACOTHERAPY AND LIFESTYLE MODIFICATION - Strzykała, Anita; Szlegiel, Igor; Gwiaździńska, Oktawia; Lewandowski, Jakub; Myszak, Denis (International Journal of Innovative Technologies in Social Science, 2026)
Aim: Hypertension in children with obesity is an increasingly common clinical problem characterized by complex pathophysiology and an early potential for target organ damage. The aim of this study was to compare the effectiveness of pharmacotherapy and lifestyle modification in the treatment of hypertension in children with obesity, taking into account the impact of both strategies on blood pressure levels, weight reduction, target organ damage, metabolic profile, treatment safety, and the durability of disease control.Materials and methods: A narrative review of the structured literature was conducted, incorporating clinical guidelines, systematic reviews, meta-analyses, randomized controlled trials, cohort studies, and cross-sectional studies retrieved from PubMed/MEDLINE, PubMed Central, Cochrane Library, Embase, and Web of Science. Publications addressing epidemiology, pathophysiology, the effectiveness of non-pharmacological and pharmacological interventions, and their impact on target organs were included.Results: The analysis indicates that lifestyle modification, including weight reduction, increased physical activity, dietary improvement, and reduced sedentary behavior, acts directly on the underlying cause of the disease and improves the metabolic profile, although it requires a longer time to achieve its full effect. Antihypertensive pharmacotherapy, particularly ACE inhibitors and ARBs, acts more rapidly and predictably, which is especially important in patients with stage 2 hypertension, symptomatic disease, target organ damage, or concomitant diabetes and chronic kidney disease.Conclusions: The greatest clinical benefit is achieved with combined treatment, which integrates rapid hemodynamic control with simultaneous intervention on obesity and other components of cardiometabolic risk. The findings indicate that non-pharmacological treatment should form the foundation of therapy in every child with obesity and hypertension, whereas pharmacotherapy should be introduced in high-risk situations or when lifestyle interventions are insufficiently effective. The optimal management model requires individualization, interdisciplinary care, and long-term monitoring.